GEOSTRATEGIC CHURN IN THE INDIAN OCEAN: POSITIONING INDIA AND THE VANILLA ISLANDS - Yaruingam, A.S.; sharma, Saurabh (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2022)
Developments over the past few decades have restructured the character of the Indian Ocean. Once playing the ‘phantom,’ when all the focus was on the Atlantic and Pacific, Indian Ocean has reclaimed the global significance that it had before renaissance. With major Sea Lines of Communication (SLOCs) traversing through its warm waters and a substantial amount of global trade dependent on it, The Indian Ocean Region has become a center for power projection. This paper is focused mainly on the South-west Indian Ocean, popularly called Vanilla Islands, and the regional power India. It critically examines the geostrategic shift taking place in the south-west Indian Ocean, and its congruence with the geopolitical dynamics of India and the Vanilla Islands.